2018
DOI: 10.5897/ajbm2018.8501
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of risk disclosures in Kenyan listed companies

Abstract: The main objective of this study was to examine the relationship between risk disclosure and firm characteristics of companies quoted on the Nairobi Securities Market. The study involved all firms that were listed on the NSE between years 2010 and 2016, except the financial institutions. Annual reports were used to determine the variables. A regression analysis was conducted using the random effect model to determine the relationship between the disclosure index and firms' characteristics. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 44 publications
5
26
2
1
Order By: Relevance
“…The significance of the coefficient improves when unweighted RDI is considered. This result supports the fifth hypothesis, H5 and earlier studies such as Buckby et al (2015) and Muturi (2018). The implication is that leverage provides a greater incentive to disclose risk information so as to access cheaper financing.…”
Section: Multi-variate Analysissupporting
confidence: 87%
See 4 more Smart Citations
“…The significance of the coefficient improves when unweighted RDI is considered. This result supports the fifth hypothesis, H5 and earlier studies such as Buckby et al (2015) and Muturi (2018). The implication is that leverage provides a greater incentive to disclose risk information so as to access cheaper financing.…”
Section: Multi-variate Analysissupporting
confidence: 87%
“…This is in line with prior studies (Tauringana and Chithambo, 2016); Domı ´nguez and G amez, 2014; Gonidakis et al, 2020). However, it contradicts the finding by Muturi (2018) Respondents B1 and B3 suggested that profit-making firms have the resources and capacity to manage risk than loss-making firms. Similarly, respondent F4 suggested that profitable firms have a high level of activities which expose them to different risks, hence, RD is useful.…”
Section: Multi-variate Analysissupporting
confidence: 79%
See 3 more Smart Citations